Avaliação da transferência de calor em fermentações alcoólicas convencional e extrativa - Almeida, Letícia Pereira (2019)
The inhibitory effect of ethanol on yeast and the temperature rise during the fermentation are the major drawbacks of the conventional ethanol production process. The use of extractive alcoholic fermentation with CO2 stripping has been investigated in order to overcome these limitations. In the present work aims conventional and extractive alcoholic fermentation with ethanol and water removal by CO2 were evaluated based on the mass and energy balances. The batch ethanol fermentations were carried out in a 10 L bubble column bioreactor at 34 ºC. First, the process kinetic parameters were estimated by modeling of conventional fermentation, considering substrate consumption, cell growth and ethanol production. The hybrid Andrews−Levenspiel model showed an excellent fit to the experimental data. From the energy balance modeling it was obtained a heat generation during fermentation 5 % lower than the heat calculated using a classical theoretical model. Subsequently, extractive batch ethanol fermentations were performed with specific CO2 flow rate (Φco2) of 0.5 and 1.0 vvm and modelled. The energetic evaluation showed that the extractive alcoholic fermentation with CO2 stripping was capable of removing the heat released in the tank, decreasing the cooling water consumption by up to 62,7%.